2022
DOI: 10.5423/ppj.oa.01.2022.0014
|View full text |Cite
|
Sign up to set email alerts
|

Application of Bacterial Endophytes to Control Bacterial Leaf Blight Disease and Promote Rice Growth

Abstract: Xanthomonas oryzae pv. oryzae (Xoo) causes bacterial leaf blight (BLB) disease in rice (Oryza sativa L.) and it is among the most destructive pathogen responsible for severe yield losses. Potential bacterial biocontrol agents (BCAs) with plant growth promotion (PGP) abilities can be applied to better manage the BLB disease and increase crop yield, compared to current conventional practices. Thus, this study aimed to isolate, screen, and identify potential BCAs with PGP abilities. Isolation of the BCAs was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Control of BLB using bactericides can potentially suppress BLB disease in the field. However, the continuous use of bactericides harms the environment, triggers resistance to pathogens, and impacts human health (Ooi et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Control of BLB using bactericides can potentially suppress BLB disease in the field. However, the continuous use of bactericides harms the environment, triggers resistance to pathogens, and impacts human health (Ooi et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…It has shown previously ability to produce indole-acetic acid (IAA) under in vitro assays (Batista et al 2018). This species belongs to the Bacillus cereus group, a subdivision of the genus Bacillus (Liu et al 2017), and certain isolates identi ed through 16S rDNA sequence analysis have attained notoriety as PGPB, especially in root development (Ooi et al 2022). Activities of phosphorus (P) and potassium (K) solubilization, ACC deaminase, hydrogen cyanide, production of phytohormones (IAA, ABA, benzyl, cytokinins, and gibberellins), siderophores, and secretion of various lytic enzymes, have been carried out by this species under in vitro or greenhouse conditions.…”
Section: Introductionmentioning
confidence: 99%
“…B. paramycoides strains have also been promising for the biocontrol of phytopathogens such as Fusarium oxysporum and Xanthomonas oryzae pv. oryzae (El-Sersawy et al 2021; Ooi et al 2022), in the degradation of acephate and methomyl widely used in agricultural pesticides (Omeiri et al 2022;Ren et al 2020), and the reduction of heavy metals to less toxic forms (Borah et al 2021) or by assisting the host as phytoremediator . Furthermore, research efforts have demonstrated its biotechnological applications.…”
Section: Introductionmentioning
confidence: 99%